Pathogenic role of the staphylococcal accessory gene regulator quorum sensing system in atopic dermatitis - Tamai, Masakazu; Yamazaki, Yuriko; Ito, Tomoka; Nakagawa, Seitaro; Nakamura, Yuumi (Frontiers in Cellular and Infection Microbiology, 2023)
The skin is home to various bacteria, archaea, fungi, and viruses, collectively referred to as the skin microbiota. Patients with certain skin diseases reportedly have unique skin “dysbiosis,” a condition involving imbalanced microbiota, suggesting that dysbiosis in the skin may be either causal or a consequence of specific skin diseases. Atopic dermatitis (AD) is the most common allergic skin disease that affects 15-20% of children and 2-10% of adults worldwide. Both intrinsic genetic factors, such as susceptibility to type 2 inflammation or skin barrier dysfunction, and extrinsic environmental factors, such as air pollen and skin microbiota, contribute to AD. Staphylococcus aureus, which does not often colonize the skin of healthy individuals, is commonly identified in the lesional skin of patients with AD and is correlated with the disease flare. However, the role of S. aureus in the pathogenesis of AD has not been elucidated. Here, we discuss the pathological behavior of S. aureus, focusing on accessory gene regulator (Agr) quorum sensing, which is a fundamental bacterial cell-to-cell interaction mechanism that affects the behavior of S. aureus and other members of the microbial community. Importantly, beyond bacteria-bacteria interactions, the Agr quorum sensing system also regulates various virulence factors, which induce type 2 and IL-17-dependent skin inflammation in the host. Furthermore, the colonization of Agr-positive S. aureus in early life accelerates the development of pediatric AD. Finally, we aim to highlight the current efforts to establish novel therapeutic methods to ameliorate or prevent AD through Agr-targeted intervention.